2006
DOI: 10.1093/bja/ael268
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic angiotensin II receptor antagonist and angiotensin-converting enzyme inhibitor treatments on neurohormonal levels and haemodynamics during cardiopulmonary bypass †

Abstract: Chronic ARA treatment resulted in more profound hypotension than ACEI treatment during CPB, and this may be associated with the blockade of angiotensin II receptors by ARA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Unfortunately, perioperative use of ACEI has been plagued with controversy, primarily because of historical reports linking it to protracted vasoplegia before, during, and after CPB. [21][22][23] Consequently, in the setting of surgery, its pattern of practice, both in the United States and internationally, is uncertain, and cessation of ACEI therapy may be as detrimental as statin and ␤-blocker withdrawal. 24,25 Therefore, the International Multicenter Study on Perioperative Ischemia (McSPI)-Epidemiology II (EPI-II) Research Group sought to prospectively characterize the pattern of perioperative ACEI use in patients having CABG surgery with CPB, to describe related hemodynamic effects, and to determine the association between the timing of ACEI renewal and in-hospital fatal and nonfatal vascular events.…”
mentioning
confidence: 99%
“…Unfortunately, perioperative use of ACEI has been plagued with controversy, primarily because of historical reports linking it to protracted vasoplegia before, during, and after CPB. [21][22][23] Consequently, in the setting of surgery, its pattern of practice, both in the United States and internationally, is uncertain, and cessation of ACEI therapy may be as detrimental as statin and ␤-blocker withdrawal. 24,25 Therefore, the International Multicenter Study on Perioperative Ischemia (McSPI)-Epidemiology II (EPI-II) Research Group sought to prospectively characterize the pattern of perioperative ACEI use in patients having CABG surgery with CPB, to describe related hemodynamic effects, and to determine the association between the timing of ACEI renewal and in-hospital fatal and nonfatal vascular events.…”
mentioning
confidence: 99%
“…In a recent case report, NE was shown to be effective when PE administration was not. 52 Nevertheless, therapy with arginine vasopressin is recommended in patients receiving angiotensin receptor blockade, 53 or where arginine vasopressin deficiency has been described as found in patients with septic shock, 54 liver failure, 55 or with vasodilatory shock after cardiac surgery 54 (Fig. 1).…”
Section: Comparison Of Norepinephrine and Phenylephrine To Manage Hypmentioning
confidence: 99%
“…Patients taking agents that antagonize this system are thus left without a key compensatory mechanism. Catecholamine resistance in patients taking ACE inhibitors and angiotensin II receptor blockers has been reported in the literature [8][9][10]. Eyraud et al [8] reported that 10 of 51 patients taking these agents had hypotension refractory to three doses of a catecholamine, and that these patients responded to the vasopressin agonist, terlipressin.…”
Section: Discussionmentioning
confidence: 99%
“…Eyraud et al [8] reported that 10 of 51 patients taking these agents had hypotension refractory to three doses of a catecholamine, and that these patients responded to the vasopressin agonist, terlipressin. In a cohort of adult patients undergoing cardiac surgery and cardiopulmonary bypass, Oh et al [9] reported that patients taking angiotensin II receptor blockers (candesartan, losartan, irbesartan, or valsartan) required higher doses of phenylepherine to maintain BP.…”
Section: Discussionmentioning
confidence: 99%